Philippine medical thesaurus on psychiatry and psychology in Tagalog behavior and behavior mechanisms - Davila, Mary Rodaline L.; Faderon, Rosalie B. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2004)
The field of medicine is very complex. Medical terminologies used here in the Philippines, which are mostly western in origin, coupled with lack of standardized tools makes it harder among doctors and patients or researchers to communicate and understand each other efficiently.
Given this predicament, the Multilingual Philippine Medical Thesaurus, which is part of the collaborative effort of the Institute of Library and Information Science, University of the Philippines Diliman, and the College of Medicine, University of the Philippines Manila, will attempt to answer the need for a unifying system between doctors and patients or researchers in terms of use of medical terms.
This study focused on the Behavior and behavior Mechanisms facet of the Psychiatry and Psychology category of the Medical Subject Headings. Data were gathered using the top-down approach, which served as a basis of the framework domain analysis. Triangulation was utilized wherein the data was checked and counter-checked in the other sources to verify the correct usage, synonymy, and other properties of a given term. 360 terms were gathered from MeSH 2004 and 155 terms were translated to Tagalog along with their pronunciation. Four respondents participated in the study. Dictionaries ranked by experts were also used to translate the medical terms to Tagalog.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Subject headings, Filipino -- Medicine; Subject headings, Filipino -- Psychology; Subject headings, Filipino -- Psychiatry; Filipino Language -- Medical Filipino